ERAP2 is associated with ankylosing spondylitis in HLA-B27-positive and HLA-B27-negative patients. - Robinson, P; Costello, M; Leo, P; Bradbury, L; Hollis, K; Cortes, A; Lee, S; Joo, K; Shim, S; Weisman, M; Ward, M; Zhou, X; et al. (BMJ Publishing Group, 2015)
The association of endoplasmic reticulum aminopeptidase (ERAP2) with ankylosing spondylitis (AS) was recently described in the large International Genetics of AS Consortium Immunochip study. Variants in ERAP2 have also been associated with inflammatory bowel disease, psoriasis, acute anterior uveitis and birdshot chorioretinopathy. Subsequent investigation demonstrated an association of ERAP2 with AS which was present when one conditioned on one of the two independent haplotypes of ERAP1 associated with AS or when HLA-B27-negative patients were analysed separately. These two analyses provide analogous evidence for the association of ERAP2 with AS inHLA-B27-negative cases because of the genetic interaction between HLA-B27 and the AS-associated ERAP1 variants in AS cases. ERAP1 and ERAP2 are located on chromosome 5q15 in the opposite orientation. The locus is challenging to analyse because of the strong linkage disequilibrium (LD) across the locus and the epistasis between ERAP1 and HLA-Balleles associated with AS. We therefore sought to investigate the association of ERAP2 with AS in HLA-B27-positive patients. This is of clinical importance because functional studies have demonstrated that the strongly AS-protective variant rs2248374 causes a functional ERAP2 protein knockout, because its G allele causes a loss of ERAP2 protein expression. There is also a variant of ERAP2 which changes its enzyme catalytic activity and specificity (rs2549782, K392A). Because this is in almost complete LD with rs2248374 (1000 Genomes D'=1.00, r^2=0.90), it is almost never translated in vivo. Further, the very strong LD between these markers means that analysis of rs2549782 for association would yield results almost identical to the results for rs2248374 presented below. Therefore, it is of relevance to determine whether the association of ERAP2 with HLA-B27-negative disease is also found in HLA-B27-positive cases, since ERAP inhibition may offer a novel therapeutic for AS